Tinjauan Literatur Sistematis: Hubungan antara Technostress dengan Burnout - Andryan, Arshya Amanta; Suminar, Dewi Retno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This systematic literature review investigates the relationship between technostress and burnout in various organizational and educational contexts. Technostress arises from excessive or imbalanced use of information technology in work or learning environments, which can adversely affect individuals' psychological well-being. Burnout, on the other hand, is a consequence of chronic stress experienced in work or educational settings. The study involves systematic steps in searching, selecting, evaluating, and synthesizing relevant literature from academic databases and other sources. Findings from the literature review reveal that technostress factors such as techno-overload, techno-invasion, techno-complexity, and others significantly contribute to individuals' levels of burnout. Recommendations for future research include the need for a mixed methods approach integrating quantitative and qualitative methods to gain deeper understanding, as well as longitudinal studies to track the development of technostress and burnout over time. This research provides a strong foundation for the development of effective policies and management practices aimed at reducing the negative impacts of technostress and enhancing individual well-being in modern work and educational environments.